MATERIAL TESTING MACHINES - Zokirov , Asror Elmurod ugli; Abdug‘aniyev , Mahmudjon Muhammadjon ugli; Mamasoliyev , Siddiqjon Tavakkal ugli (Educational Research in Universal Sciences, 2023)
Materials testing is based on theoretical knowledge. Buildings, structures, bridges, machines and mechanisms, spaceships and rockets, clothing and other aggregates are built, made, prepared and sewn based on the results of the Material Test.